The Arian bishops from the Balkans (Research Announcements "Heritage BG", 2025)
Arianism, its role and importance for the development of Christianity and the religious policy of emperors, have been the subject of different studies. However, one important aspect of the history of this heresy remains understudied – the role of the Arian bishops from the Balkans in the development and political influence of this heresy. As early as the first half of the 4th century, Arianism spread throughout the Roman Empire. Many of the bishops of the Balkan Roman provinces sided with the Arians from the beginning of the religious conflict and began to take an active part in theological disputes, but so far their history and the role that they played have not been studies. Six Arian bishops from the Balkans are known to be close advisers to emperors, one of the most educated Christians of their time, charismatic leaders who left behind a literary legacy (which has not reached us) and followers. One of them, Demophilus of Augusta Trayana, managed to rise to the patriarch of Constantinople. The purpose of the proposed report is to present the main activities of Bishops Ursakius of Singidunum, Valens of Mursa, Palladius of Ratiaria, Auxentius of Durostorum, Demophilus of Augusta Traiana and Maximinus of Durostorum, as well as their influence on the development of the Arian conflict. References:Primary Sources:Avksentiy Dorostorskiy. „O vere, zhizni i konchine Ulyfilы“, (per. i komment.) G. E. Zaharova), Vestnik PSTGU. Seria II 4 (41) (2011), 105–116Actes du concile d’Aquilée, R. Gryson (ed.) [Sources chrétiennes 267] (Paris, 1980), 330-383.Ambrose of Milan Sancti Ambrosi Opera Pars X, Epistulae et Acta Tom. III: Epistularum Liber Decimus, Epistulae extra Collectionem, Gesta Concili Aquileiensis, M. Zelzer (ed.) [Corpus Scriptorum Ecclesiasticorum Latinorum 82.3], (Vienna,1982) 126-140.Athanasius of Alexandria, Epistula ad Episcopos Aegypti et Libyae, K. Metzler (ed.) Athanasius: Werke I.1 (Berlin, 1996–2000), 39–64. Translated in A. Robertson (ed.) (1892) St. Athanasius: Select Works and Letters, Select Library of Nicene and Post-Nicene Fathers, Second Series, vol. 4, (Oxford), 222–235.De fide ad Gratianum Augustum, O. Faller (ed.) [Corpus Scriptorum Ecclesiasticorum Latinorum 78] (Wien 1962).Dissertatio Maximini contra Ambrosium – Kauffmann, F. (tr.), Aus der Schule de Wulfila, Texte und Untersuchungen zur altegermanidchen Religiousgeschichte. Texte 1 (Strasburg, 1899).Epistulae extra collectionem, M. Zelzer (ed.) [Corpus Scriptorum Ecclesiasticorum Latinorum 82.3] (Wien, 1982), 145-311.Gesta councilii Aquileiensis, M. Zelzer (ed.) [Corpus Scriptorum Ecclesiasticorum Latinorum 82.3], (Wien, 1982), 313-368.Gesta councilii Aquileiensis, ed. M. Zelzer [Corpus Scriptorum Ecclesiasticorum Latinorum 82.3] (Wien 1982), 313-368.Hilarius Pictaviensis, Collectionea antiariana Parisina, ed. A. Feder, Corpus Scriptorum Ecclesiasticorum Latinorum 65, Wien – Leipzig 1916.Philostorgius, Historia Ecclesiastica, J. Bidez (ed.) (1981) Philostorgius: Kirchengeschichte, GCS, 3rd edn, rev. by F. Winkelmann. P. R. Amidon (tr.) Philostorgius: Church History (Atlanta, Georgia, 2007)Rufinus, Historia Ecclesiastica (Books 10-11) E. Schwartz, T. Mommsen and F. Winkelmann (eds.) (1999), Eusebius Werke, Band 2: Die Kirchengeschichte, 2nd edn, GCS n.f. 6 (Berlin), 957-1040. The Church History of Rufinus of Aquileia, Books 10 and 11, P. R. Amidon (tr.) (Oxford, 1997)Scolies Ariennes sur le concile d’Aquilée, R. Gryson (ed.) [Sources chrétiennes 267] (Paris, 1980), 237–251.Sermo contra Auxentium de basilicis tradendis. (PL. 16. Col. 1049-1062)Sokrates Scholasticus, Historia ecclesiastica, Günther Christian Hansen (ed.), GCS N.F. 1 (Berlin, 1995).Sozomenos, Historia ecclesiastica, Joseph Bidez and Günther Christian Hansen (eds), GCS 50 (Berlin, 1960); Ernst Walford (tr.), The ecclesiastical history of Sozomen, comprising a history of the church form A.D. 324 to A.D. 440 (London, 1855).Theodoret, Historia ecclesiastica, Léon Parmentier and Günther Christian Hansen (eds), Theodoret Kirchengeschichte, GCS N. F. 5, (3rd edn, Berlin, 1998); Blomfield Jackson (tr.), ‘The Ecclesiastical history, dialogues, and letters of Theodoret’, in Henry Wace and Philip Schaff (eds), Theodoret, Jerome, Gennadius, Rufinus: Historical Writings, NPNF 3 (Oxford 1892, repr. 1995), 33-160.Secondary sources:Gerdzhikova 2020d: Gerdzhikova, Zlatomira. Paladiy ot Ratsiaria. Arianskiyat glas ot Balkanite. In: Glasove i slike. Oblici komunikacije naSrednovekovnom Balkanu (IV–XVI vek) Beograd, 19-42.Barnes 1993: Barnes, Timothy. Athanasius and Constantius. Theology and Politics in the Constantinian Empire. London.Gerdzhikova 2020a: Gerdzhikova, Zlatomira. Ursacius, bishop of Singidunum, and Valens, bishop of Mursa https://labalkans.org/en/labedia/religion/christianity/ursacius-and-velensGerdzhikova 2020b: Gerdzhikova, Zlatomira. Auxentius, bishop of Durostorum https://labalkans.org/en/labedia/religion/christianity/auxentius-of-durostorumGerdzhikova 2020c: Gerdzhikova, Zlatomira. Maximinus, bishop of Durostorum https://labalkans.org/en/labedia/religion/christianity/maximinus-of-durostorumHanson 1988: Hanson, R.P.C. The search for the Christian doctrine of God: the Arian controversy, 318-381 AD. Edinburgh.Kauffmann 1899: Kauffmann F. Aus der Schule de Wulfila. Strasburg.Kelly 1982: Kelly J.N.D. Early Christian Creeds. Routledge.Lenox-Conyngham 1982: Lenox-Conyngham, A. The Topography of the Basilica Conflict of A.D. 385/6 in Milan. – Zeitschrift für Alte Geschichte, No. 31.3, 353-363.Liebeschuetz 2005: Liebeschuetz John Hugo (ed.). Ambrose of Milan. Political Letters and Speеches. Liverpool, 201–254.McLynn 1994: McLynn, Neil. Ambrose of Milan: Church and Court in a Christian Capital. California.Teske 2009: Teske, Ronald. Augustine of Hippo: philosopher, exegete, and theologian. A second collection of Esseys. Marquette University Press.Williams 1995: Williams, Daniel. Ambrose of Milan and the End of the Arian-Nicene Conflicts. Oxford.Zeiller 1918: Zeiller Jacques. Les origines chrétiennes dans les provinces danubiennes de l’Empire romain. Paris.
Keywords: Ursacius of Singidunum; Valens of Mursa; Palladius of Ratiaria; Auxentius of Durostorum; Maximinus of Durostorum; Araianism; Balkans